BENTUK-BENTUK WADAH PENGUBURAN DALAM SISTEM KEPERCAYAAN MASYARAKAT MAMASA, SULAWESI BARAT - Bernadeta AKW (Balai Arkeologi Provinsi Sulawesi Selatan, 2009)
Mamasa is one of the districts in West Sulawesi that many store various forms of culture and tradition which is still maintained. Cultural forms such as traditional houses and other burial containers and ancestral traditions that run in the context of belief systems. Survey indicates there are several types of burial containers in Mamasa